2008
DOI: 10.1371/journal.pgen.1000118
|View full text |Cite
|
Sign up to set email alerts
|

Novel Association of ABO Histo-Blood Group Antigen with Soluble ICAM-1: Results of a Genome-Wide Association Study of 6,578 Women

Abstract: While circulating levels of soluble Intercellular Adhesion Molecule 1 (sICAM-1) have been associated with diverse conditions including myocardial infarction, stroke, malaria, and diabetes, comprehensive analysis of the common genetic determinants of sICAM-1 is not available. In a genome-wide association study conducted among 6,578 participants in the Women's Genome Health Study, we find that three SNPs at the ICAM1 (19p13.2) locus (rs1799969, rs5498 and rs281437) are non-redundantly associated with plasma sICA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
301
3
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(327 citation statements)
references
References 52 publications
14
301
3
9
Order By: Relevance
“…However, it is of great interest that ABO has been associated recently in a number of hypothesis-free genome-wide associations with a diverse set of phenotypes, such as pancreatic cancer or plasma levels of intercellular adhesion molecule-1. 36,37 These data suggest that ABO effects on these phenotypes may indeed underlie a common mechanism that still needs to be determined.…”
Section: Discussionmentioning
confidence: 92%
“…However, it is of great interest that ABO has been associated recently in a number of hypothesis-free genome-wide associations with a diverse set of phenotypes, such as pancreatic cancer or plasma levels of intercellular adhesion molecule-1. 36,37 These data suggest that ABO effects on these phenotypes may indeed underlie a common mechanism that still needs to be determined.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, carriers of blood group A may have diminished tumor immune response due to reduced ability to recognize and attack tumor cells that express Forssmann antigen. Finally, it should be noted that several studies have demonstrated an association between ABO genotype and altered levels of soluble E-selectin, ICAM-1, and tumor necrosis factor-alpha (Pare et al, 2008;Paterson et al, 2009a, Paterson et al, 2009b which also may suggest potential role of ABO in cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that ABO blood group antigen may alter the systemic inflammatory response. Genome-wide association studies have found an association between genetic variation in the first intron of the ABO genes and circulation levels of serum tumor necrosis factor alpha, 47 soluble intracellular adhesion molecule 48 and plasma levels of alkaline phosphatase. 49 Acute pancreatitis may be a complication of acute hepatitis infection.…”
Section: Discussionmentioning
confidence: 99%